Correction: Fall prediction in a quiet standing balance test via machine learning: Is it possible? - Juliana Pennone; Natasha Fioretto Aguero; Daniel Marczuk Martini; Luis Mochizuki; Alexandre Alarcon do Passo Suaide (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0296355.].